S97 Management of early stage lung cancer in the elderly: an observational study. (15th November 2017) - Kennedy, MPT; Franks, K; Brunelli, A; Callister, MEJ
Abstract : Introduction: Elderly patients are less likely to receive radical treatment for lung cancer. Palma et al (2010) demonstrated an increase in radical treatment rates for patients aged ≥75 years in Holland following the introduction of Stereotactic Ablative Radiotherapy (SABR), without reduction in surgical resections. This was associated with improved overall survival. There are international differences in radical treatment rates and outcomes in lung cancer. We aim to evaluate the changes in lung cancer treatment and outcomes following the introduction of SABR in the UK. Methods: This is a retrospective observational study at a large UK teaching hospital. Data for patients diagnosed over seven years (2008–2014) were analysed from a local dataset maintained for the National Lung Cancer Audit. SABR was introduced for lung cancer in Leeds in 2010. Statistical analyses were performed using Chi-square, t-test and Kaplan Meier survival analysis. Results: There were 1874 new diagnoses of lung cancer in patients aged ≥75 years, accounting for 45.3% of all new diagnoses. Comparing patients≥75 years pre-SABR (2008–2009) and post-SABR (2011–2014), there was an increase in the proportion of early stage disease (stage I-IIA 22.5% to 29.2%, p=0.0054). Of the 502 patients with early stage disease, there was no change in performance status (PS 0%–2 68.4% to 63.3%, p=0.2468) or age at diagnosis (median (IQR) 81.1 (78.0–84.3) to 80.9 (77.7–85.1) years, p=0.7422). Rates of radical radiotherapy/SABR (12.2% to 39.2%, p<0.001) have increased, while surgical resections (28.9% to 28.5%, p=1.000) have remained stable and the proportion of patients receiving palliative treatment/best supportive care (BSC) has decreased (58.8% to 32.3%, p<0.001) (figure 1 ). Median overall survival has increased (518 to 687 days, p=0.0016). Discussion: The proportion of elderly patients being diagnosed with early stage lung cancer is increasing. There has been no significant change in the demographics of those with early stage disease. Following the introduction of SABR in 2010, there has been an increase in radical radiotherapy treatment for elderly patients with early stage disease, with no sustained change in surgical resection rates and increase in overall rates of radical treatment. This was associated with a significant improvement in overall survival.